Evaluation of placenta and fetal lung using shear wave elastography in gestational diabetes mellitus: An innovative approach - Bayraktar, Burak; Golbasi, Hakan; Omeroglu, Ibrahim; Golbasi, Ceren; Tuncer Can, Sevim; Ince, Onur; Bayraktar, Miyase Gizem; Ozer, Mehmet; Ekin, Atalay (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
This study aims to investigate placental and fetal lung stiffness in pregnant women with and without gestational diabetes, considering the well-established delay in fetal lung maturation associated with gestational diabetes.This prospective cohort study was conducted at a tertiary center and included pregnant women who underwent a 75-gram oral glucose tolerance test between 24–28 weeks of gestation. Elastography measurements were performed using point shear wave elastography (pSWE).The study included 60 pregnant women diagnosed with gestational diabetes and 60 pregnant women in the control group. The SWE velocity of the peripheral placenta, central placenta, and lung was higher in the gestational diabetes group compared to the control group. Furthermore, the SWE velocity of the peripheral placenta, central placenta, and lung was higher in newborns with neonatal respiratory morbidity. Based on the ROC analysis of patients with gestational diabetes, the AUC for lung SWE velocity was 0.88 (cut-off 12.4 kPa, 95% CI: 0.77–0.99, p<0.001) with a sensitivity of 71.4% and specificity of 95.6% for predicting neonatal respiratory morbidity.Fetal placental and lung stiffness increase in fetuses of pregnant women with diabetes. Moreover, higher fetal lung stiffness during the fetal period is associated with increased neonatal respiratory morbidity.
Keywords: shear wave elastography; stiffness; fetal lung elastography; gestational diabetes; neonatal respiratory morbidity